Is mobile learning a resource in higher education? Data evidence from an empirical research in Ticino (Switzerland) - Emanuele Rapetti; Anna Picco-Schwendener; Sara Vannini (Je-LKS: Journal of E-Learning and Knowledge Society, 2011)
Nowadays mobile devices are highly present and well integrated in students’ everyday life. People use them for communication, information retrieval and exchange, entertainment, and even for business. But what can be said about learning? This article tries to figure out the importance of mobile devices for students in their learning experience: on one side by giving an insight into current researches in the field of mobile learning, and on the other side by providing data evidence collected in two higher education institutions of Ticino in Switzerland. By analyzing questions such as, which mobile devices do students use for learning, what for, how do they use them and how keen they are to adopt their mobile tools to support their formal learning activities at university. We also explore whether a transfer from informal usage of mobile devices in students’ everyday life to more formal applications in learning processes has taken place. So far, this does not seem to be the case. Most students use mobile devices to communicate with peers for learning-related purposes and very little to directly learn through them.